How to Promote Innovative Work Behavior among Academics - Ibus, Salbeha; Wahab, Eta; Ismail, Fadillah (International Journal of Psychosocial Rehabilitation, 2020)
Knowledge sharing has been proven to contribute potential benefits to organizations. Nevertheless, studies on the impact of knowledge sharing on innovative work behavior were inadequately explored. This study attempts to identify the influence of knowledge sharing on innovative work behavior and the mediator role of self-efficacy. Three hundred fifty samples were collected from the academics and analyzed through correlation and structured equation modeling techniques. The findings showed that knowledge sharing was significantly affected by innovative work behavior (β = 0.34, p